Efektivitas Ketua Komite Audit dan Kinerja Perusahaan: Peran Moderasi Pengungkapan Keberlanjutan - Vera Maulidina; Rita Wijayanti (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2024)
This study aims to analyze the role of moderation of sustainability disclosure in relation to the effectiveness of the chairman of the audit Committee which consists of accounting expertise, tenure, monitoring expertise, expertise experience of the chairman of the audit Committee on the performance of the company. Through data collection sourced from the IDX website, there are 21 companies with a total of 139 data. This study uses multiple linear regression analysis method. Researchers used the IDX website to collect data, then processed using SPSS version 25.0. Based on the results of the study concluded that the variable accounting expertise of the chairman of the audit committee affect the performance of the company, while the variable tenure of the chairman of the audit committee, monitoring expertise of the chairman of the audit committee, expertise experience of the chairman of the audit committee does not affect the performance of the company. The variable of sustainability disclosure is able to moderate the influence of experience expertise of the chairman of the audit Committee on the performance of the company, while the disclosure of sustainability is not able to moderate the influence of accounting expertise, tenure, monitoring expertise of the chairman of the audit Committee on the performance of the company.